Investigation of gold nanorod monomer biosensors for label free molecule detection - Hasan, Rakib; Rabbi, Fazle (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.